Analisis Korelasi Faktor Gaya Hidup Terhadap Indikator Kesehatan Menggunakan Metode Shapiro-Wilk dan Spearman - Mohd Fadli Ariansyah; Eka Pandu Cynthia (Prosiding Seminar Nasional Ilmu Teknik, 2025)
Lifestyle changes, such as smoking habits, low physical activity, and suboptimal sleep patterns, have the potential to affect various health indicators. However, empirical evidence showing a direct link between lifestyle factors and objective health indicators still shows varying results. This study aims to analyze the relationship between lifestyle factors and health indicators in adult respondents, in an effort to provide an empirical picture of behavioral factors related to health conditions. This study used a quantitative approach with a cross-sectional observational analytic design. Data were obtained from 94 respondents who had complete lifestyle data and health examination results. Lifestyle factors analyzed included smoking habits, exercise frequency, and sleep duration, while health indicators included body mass index (BMI), systolic and diastolic blood pressure, blood sugar levels, cholesterol, uric acid, and pulse rate. Data analysis was performed using descriptive statistics, the Shapiro–Wilk normality test, and the Spearman correlation test according to the characteristics of the data distribution. The results showed that smoking habits were significantly associated with diastolic blood pressure (p < 0.05), exercise frequency was significantly associated with BMI and systolic blood pressure (p < 0.05), and sleep duration was significantly associated with uric acid levels (p < 0.05). Meanwhile, the relationship between lifestyle factors and other health indicators did not show statistical significance. These findings indicate that the influence of lifestyle on health is specific to certain indicators and is not evenly distributed across all health parameters. This study concludes that identifying lifestyle factors relevant to certain health indicators is important as a basis for formulating more targeted health promotion strategies.